Performance losses following threefold volume increases in soccer-specific training and in small-sided games - Hourcade, J.-C.; Noirez, P.; Sidney, M.; Toussaint, J.-F.; Desgorces, F.-D. (Science and Medicine in Football, 2019)
Objectives: The present study analyzes the effects of volume increase on physical performances in soccer-specific exercises performed at high intensity. Methods: 12 young professional players performed three types of soccer-specific exercise: one small-sided game (SSG) and two soccer-specific training (SST: repeated sprints and aerobic runs). Each type of exercise was performed twice, at low and high training volume. Acute and delayed sessions` effects were assessed by changes in exercise heart-rate (HR) and blood lactate, counter-movement jumps (CMJ), speed and distance achieved during a final game performed after the soccer-specific exercises. Results: In SSG, the volume increase enhanced the time spent in the highest HR zone (P=0.027) and blood lactate concentration (P=0.018). Speed and distance achieved in the final game were lower after SSG than after aerobic-SST exercise (P<0.05). The next morning CMJ decreased after SST exercises (P<0.001). Sessions` HR was correlated with running distance (r=0.65, P=0.006) and the next morning changes in sprint density was correlated with CMJ performance (r=0.56, P=0.01). Conclusion: Acute negative effects of volume increase appeared after SSG while delayed negative effects appeared after SST. The present study focused on short terms exercise-induced effects; more studies remain required for controlling the full range of needed recovery durations.